Reliability Analysis of Modern Power Systems - Saket R.K.; Sanjeevikumar P. (My University, 2025)
A reader-friendly introduction to reliability analysis and its power systems applications The subset of probability theory known as reliability theory analyzes the likelihood of failure in a given component or system under given conditions. It is a critical aspect of engineering as it concerns systems of all kinds, not least modern power systems, with their essential role in sustaining the technologies on which modern life relies. Reliability Analysis of Modern Power Systems is a thorough, accessible book introducing the core concepts of reliability theory as they apply to power systems engineering, as well as the advanced technologies currently driving new frontiers in reliability analysis. It is a must-own for anyone looking to understand and improve the systems that power our world. Readers will also find: • Detailed discussion of reliability modeling and simulation of composite systems using Typhoon HIL 404 • Reliability assessment of generation systems, transmission systems, distribution systems, and more • Information on renewable energy integration for more sustainable power grids Reliability Analysis of Modern Power Systems is ideal for professionals, engineers, and researchers in power system design and reliability engineering, as well as for advanced undergraduate and graduate students in these and related subjects. © 2024 by The Institute of Electrical and Electronics Engineers, Inc. All right reserved.